Argumentation in Training Courses - Form and Function - Chefneux Gabriela (My University, 2019)
The paper uses as its theoretical framework the Membership Categorization Analysis, a way of understanding how interlocutors interpret and give meaning to reality. The concepts underlying the analysis are members, categories, categorization devices, and categorization methods. The data drawn upon are seven interviews recorded with students from the Faculty of Letters at Transilvania University of Brașov. The paper investigates the values the respondents associate with being a student by resorting to categories, categorization devices (considered as expressing moral principles and attitudes), and categorization methods.